Long-term coding of personal and universal associations underlying the memory web in the human brain - Emanuela De Falco (Nature Portfolio, 2016)
Neurons in the medial temporal lobe change their firing patterns as people learn to pair items together, yet it is unclear if this pairing lasts. Here, authors find that single medial temporal lobe neurons in humans tend to respond similarly to items that are closely conceptually related.